Development of a Web-Based Automated Production Inventory System - Rafi Rasyid Parmana; Ivan De Nerol; Ester Angeline; Dhafa Kamil (Batrisya Education, 2024)
This research focuses on the design of an automatic counting system for production items using the ESP32 microcontroller and E18-D80NK sensor. The main objective of the study is to address inventory issues, particularly in the context of manual counting of production items, which is susceptible to shortages and inaccuracies. The proposed automatic counting device aims to provide a solution to enhance employee performance efficiency and reduce the risk of human errors. The integration of the ESP32 microcontroller as a data processor and the E18-D80NK sensor as an information capture device will allow easy access to calculation results through a website interface. The primary advantage of this system is its ability to prevent potential data forgery in production and provide more accurate calculation results. With data storage on a website platform, tracking production history becomes more effective, enabling in-depth analysis of overall production performance. This research proposes an integrated solution to enhance efficiency, transparency, and accuracy in the production counting process. With the implementation of this technology, it is expected that the automated production system can be a strategic step towards improving productivity and the reliability of production information.